Mercury-based Traditional Medicines: Chemical Composition and Mineral-herb Mixtures Differ from Toxic Mercury Compounds on Hepatic Cytochrome P450 - Nie, Yu; Xu, Shang-Fu; Lu, Yan-Liu; Zhao, Xiu-Rong; Li, Cen; Wei, Li-Xin; Liu, Jie (Recent Progress in Science and Technology Vol. 1, 2023)
Zuotai (\(β\)-HgS)-containing 70 Wei-Zhen-Zhu-Wan (70W, Qishiwei, Rannasangpei) is a Chinese ethnomedicine at Qinghai-Tibet region for cardiovascular and gastrointestinal diseases. We have found that 70W protected against CCl4 hepatotoxicity. Utilizing cytochrome P450 (CYP), CCl4 is metabolized to create reactive metabolites. It is unclear whether 70W has any impact on CYPs, and any such impact should be compared to harmful mercury compounds for safety assessment. In this experiment, Mice were given clinical doses of 70W (0.15-1.5 g/kg, po), Zuotai (30 mg/kg, po), and compared to HgCl2 (33.6 mg/kg, po) and MeHg (3.1 mg/kg, po) for 7 days. Liver RNA and protein were isolated for qPCR and Western-blot analysis. The findings of this study showed that 70W and Zuotai had no effects on hepatic mRNA expression of Cyp1a2, Cyp2b10, Cyp3a11, Cyp4a10 and Cyp7a1, and corresponding nuclear receptors [aryl hydrocarbon receptor (AhR), constitutive androstane receptor (CAR), pregnane X receptor (PXR), peroxisome proliferator-activated receptor-\(α\) (PPAR\(α\)); farnesoid X receptor (FXR)]. In comparison, HgCl2 and MeHg increased mRNA expression of Cyp1a2, Cyp2b10, Cyp4a10 and Cyp7a1 except for Cyp3a11, and corresponding nuclear receptors except for PXR. Western-blot confirmed mRNA results, showing increases in CYP1A2, CYP2B1, CYP2E1, CYP4A and CYP7A1 by HgCl2 and MeHg only, and all treatments had no effects on CYP3A. In contrast to HgCl2 and MeHg, Zuotai and Zuotai-containing 70W had little impact on the hepatic CYPs and associated nuclear receptors. Thus, HgS-herb mixtures differ from toxic Hg compounds on hepatic P450 and nuclear receptors.